Organocatalytic asymmetric allylic amination of Morita–Baylis–Hillman carbonates of isatins - Zhang, Hang; Zhang, Shan-Jun; Zhou, Qing-Qing; Dong, Lin; Chen, Ying-Chun (Beilstein Journal of Organic Chemistry, 2012)
The investigation of a Lewis base catalyzed asymmetric allylic amination of Morita–Baylis–Hillman carbonates derived from isatins afforded an electrophilic pathway to access multifunctional oxindoles bearing a C3-quaternary stereocenter, provided with good to excellent enantioselectivity (up to 94% ee) and in high yields (up to 97%).
Keywords: allylic amination; asymmetric organocatalysis; Morita–Baylis–Hillman carbonates; 2-oxindoles; quaternary chiral center

(untitled) - Bernard, K.; Bogliolo, S.; Ehrenfeld, J. (Br. J. Pharmacol., 2005)

(untitled) - Serradeil-Le Gal, C.; Derick, S.; Brossard, G.; Manning, M.; Simiand, J.; Gaillard, R.; Griebel, G.; Guillon, G. (Stress, 2003)

(untitled) - Ochi, M.; Kawasaki, K.; Kataoka, H.; Uchio, Y.; Nishi, H. (Biochem. Biophys. Res. Commun., 2001)

(untitled) - Chevolot, L.; Chevolot, A. M.; Gajhede, M.; Larsen, C.; Anthoni, U.; Christophersen, C. (J. Am. Chem. Soc., 1985)

(untitled) - Anthoni, U.; Chevolot, L.; Larsen, C.; Nielsen, P. H.; Christophersen, C. (J. Org. Chem., 1987)

(untitled) - Takayama, H.; Mori, I.; Kitajima, M.; Aimi, N.; Lajis, N. H. (Org. Lett., 2004)

(untitled) - Shen, K.; Liu, X.; Lin, L.; Feng, X. (Chem. Sci., 2012)

(untitled) - Mouri, S.; Chen, Z.; Mitsunuma, H.; Furutachi, M.; Matsunaga, S.; Shibasaki, M. (J. Am. Chem. Soc., 2010)

(untitled) - Yang, Z.; Wang, Z.; Bai, S.; Shen, K.; Chen, D.; Liu, X.; Lin, L.; Feng, X. M. (Chem.–Eur. J., 2010)

(untitled) - Shen, K.; Liu, X.; Wang, G.; Lin, L.; Feng, X. (Angew. Chem., Int. Ed., 2011)

(untitled) - Cheng, L.; Liu, L.; Wang, D.; Chen, Y.-J. (Org. Lett., 2009)

(untitled) - Zhou, F.; Ding, M.; Liu, Y.-L.; Wang, C.-H.; Ji, C.-B.; Zhang, Y.-Y.; Zhou, J. (Adv. Synth. Catal., 2011)

(untitled) - Bui, T.; Hernández Torres, G.; Milite, C.; Barbas, C. F., III (Org. Lett., 2010)

(untitled) - Bui, T.; Borregan, M.; Barbas, C. F., III (J. Org. Chem., 2009)

(untitled) - Qian, Z.-Q.; Zhou, F.; Du, T.-P.; Wang, B.-L.; Ding, M.; Zhao, X.-L.; Zhou, J. (Chem. Commun., 2009)

(untitled) - Lesma, G.; Landoni, N.; Pilati, T.; Sacchetti, A.; Silvani, A. (J. Org. Chem., 2009)

(untitled) - Jung, H. H.; Buesking, A. W.; Ellman, J. A. (Org. Lett., 2011)

(untitled) - Cao, Z.-Y.; Zhang, Y.; Ji, C.-B.; Zhou, J. (Org. Lett., 2011)

(untitled) - Guo, Q.-X.; Liu, Y.-W.; Li, X.-C.; Zhong, L.-Z.; Peng, Y.-G. (J. Org. Chem., 2012)

(untitled) - Yan, W.; Wang, D.; Feng, J.; Li, P.; Wang, R. (J. Org. Chem., 2012)

(untitled) - Yan, W.; Wang, D.; Feng, J.; Li, P.; Zhao, D.; Wang, R. (Org. Lett., 2012)

(untitled) - Liu, T.-Y.; Xie, M.; Chen, Y.-C. (Chem. Soc. Rev., 2012)

(untitled) - Peng, J.; Huang, X.; Cui, H.-L.; Chen, Y.- C. (Org. Lett., 2010)

(untitled) - Huang, X.; Peng, J.; Dong, L.; Chen, Y.-C. (Chem. Commun., 2012)

(untitled) - Zhang, S.-J.; Cui, H.-L.; Jiang, K.; Li, R.; Ding, Z.-Y.; Chen, Y.-C. (Eur. J. Org. Chem., 2009)

(untitled) - Lin, A.; Mao, H.; Zhu, X.; Ge, H.; Tan, R.; Zhu, C.; Cheng, Y. (Chem.–Eur. J., 2011)

(untitled) - Sun, W.; Ma, X.; Hong, L.; Wang, R. (J. Org. Chem., 2011)

(untitled) - Pei, C.-K.; Zhang, X.-C.; Shi, M. (Eur. J. Org. Chem., 2011)

(untitled) - Chen, Y. K.; Yoshida, M.; MacMillan, D. W. C. (J. Am. Chem. Soc., 2006)

(untitled) - Peng, J.; Huang, X.; Jiang, L.; Cui, H.-L.; Chen, Y.-C. (Org. Lett., 2011)

(untitled) - Waldmann, H.; Khedkar, V.; Dückert, H.; Schürmann, M.; Oppel, I. M.; Kumar, K. (Angew. Chem., Int. Ed., 2008)

(untitled) - Cui, H.-L.; Peng, J.; Feng, X.; Du, W.; Jiang, K.; Chen, Y.-C. (Chem.–Eur. J., 2009)

(untitled) - Furukawa, T.; Kawazoe, J.; Zhang, W.; Nishimine, T.; Tokunaga, E.; Matsumoto, T.; Shiro, M.; Shibata, N. (Angew. Chem., Int. Ed., 2011)

(untitled) - Hu, Z. K.; Cui, H. L.; Jiang, K.; Chen, Y. C. (Sci. China, Ser. B: Chem., 2009)

(untitled) - Bentley, S. A.; Davies, S. G.; Lee, J. A.; Roberts, P. M.; Russell, A. J.; Thomson, J. E.; Toms, S. M. (Tetrahedron, 2010)

(untitled) - Benfatti, F.; Cardillo, G.; Contaldi, S.; Gentilucci, L.; Mosconi, E.; Tolomelli, A.; Juaristi, E.; Reyes-Rangel, G. (Tetrahedron, 2009)